Unmet health-related social needs are associated with pain outcomes among midlife and older adults - Victoria H. Davis; Elizabeth J. Brines; Mary R. Janevic (Frontiers in Pain Research, 2026)
Introduction Chronic pain affects over one-third of U.S. older adults, and particularly socioeconomically constrained populations. Few studies examine how unmet social needs related to the social determinants of health, including food, housing, utilities, transportation, and social support, are linked to pain. This study assessed whether cumulative and individual unmet social needs are associated with pain outcomes in a predominantly Black/African American sample of adults aged 50 years and older with chronic pain recruited from an underserved urban setting. Methods We pooled pre-intervention data from two randomized controlled trials of community health worker-led behavioral interventions. Multivariable linear regression examined associations of cumulative and individual unmet social needs with pain intensity, pain interference, and pain self-efficacy. Results Among 438 participants, the mean age was 67.5 years, 87% ( n = 380) were female, 77% ( n = 338) identified as Black/African American, and 54% ( n = 237) reported one or more unmet social needs. In adjusted regression models, participants with greater cumulative unmet social needs (three or more) experienced greater pain intensity ( B = 0.75, p = .010), pain interference ( B = 3.24, p = .002), and lower pain self-efficacy ( B = −2.04, p = .006). Food access challenges were associated with all three outcomes; transportation difficulties were linked with greater pain interference and lower self-efficacy; and insufficient social support was associated with greater pain intensity and greater pain interference ( p < .05). Housing and utility payment difficulties were not associated with pain outcomes. Conclusion Cumulative and individual unmet social needs are associated with worse pain outcomes among midlife and older adults with chronic pain.